TAWARAN KONSEP AL-SHULHU DALAM MEDIASI KASUS PERCERAIAN PADA MAHKAMAH SYAR’IYAH JANTHO - Putri Munawwarah; Zaiyad Zubaidi (AHKAMUL USRAH: Jurnal S2 Hukum Keluarga dan Peradilan Islam, 2021)
The research was motivated by the lack of success rate of mediation in divorce cases in the Jantho Sharia Court. This research aims to increase the potential for peace in divorce cases in the Jantho Sharia Court using the implementation of al-Shulhu's concept. This qualitative research was based on field research and library research methodologies. The data were in the form of relevant documents that have not been formally published and relevant literatures. The data were then analyzed using descriptive analysis techniques. By this research, the writer offers al-Shulhu as a concept of peace that can be applied by judges in trials in Jantho Sharia Court. The conditions and pillars that must be fulfilled makes the concept of al-Shulhu have coercive and binding power between both husband and wife. This is because the legal consequences contained in the concept of al-Shulhu are the same as the legal consequences in agreements which give rise to rights and obligations for the parties involved in the agreement.